Bus network characteristics for promoting sustainable urban mobility systems - Petrelli, Marco (International Conference “Environmental Engineering”, 2023)
The present study deals with the systematic analysis of the bus network characteristics in many Italian cities and towns, characterized by a supply of public transport services mainly based on buses. The aim of the analysis is to derive the key characteristics for providing effective public transport services. The database built for the study is related to 54 municipalities, with a population from 80,000 to 360,000 inhabitants, and it is composed by a large set of indicators about supply and demand of the bus services network and of the territorial characteristics of the municipalities. The results of the analysis permit to underline the existence of very different condition about level of provided services, impacting on the level of demand using the public transport. These differences are not only related to the territorial characteristics but are also due to completely different characteristics of the supply.